Lean Operations Strategy Model for Improving Efficiency and Cost Management in Tech Distribution Facilities - Kujore Victoria Omotayo,; Abel Chukwuemeke Uzoka,; Chinelo Harriet Okolo,; Oluwasanmi Segun Adanigbo,; Florence Ifeanyichukwu Olinmah, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This paper proposes a tailored lean operations strategy model aimed at enhancing efficiency and cost management within technology distribution facilities. Recognizing the unique challenges posed by high product velocity, inventory sensitivity, and demand volatility in tech supply chains, the model integrates core lean principles, value specification, waste elimination, flow, and continuous improvement, adapted to this dynamic environment. The model architecture comprises real-time data inputs, cross-functional collaboration, and standardized workflows, supported by enabling technologies and cultural enablers. Process streamlining tools such as 5S, Kanban, and value stream mapping systematically target non-value-adding activities across inbound logistics, order fulfillment, and dispatch operations. The model embeds feedback mechanisms, including visual management and operational KPIs, to sustain iterative learning and improvement. Implementation considerations address organizational culture, technology integration, and risk management, emphasizing leadership support and phased adoption. Theoretically, this framework extends lean thinking to complex, fast-paced distribution contexts, while practically providing actionable guidance for managers and strategists in high-tech logistics. The paper concludes with recommendations for empirical validation and exploration of emerging technologies and sustainability integration, positioning the model as a comprehensive roadmap for achieving operational excellence in technology distribution.
Keywords: Lean operations; technology distribution; supply chain efficiency; waste elimination; continuous improvement; cost management